2022
DOI: 10.1021/acs.iecr.2c01620
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Effect of the Surfactant on the Single Bubble Rising in Stagnant Surfactant Solutions and a Mathematical Model for the Bubble Motion

Abstract: Bubble behavior has a significant effect on the gas−liquid mass transfer in bubbly flows. In this study, the bubble rising velocity and bubble shape in ultrapure water and surfactant solutions are experimentally measured by high−speed photography. The bubble velocity decreases and the bubble shape tends to be spherical due to the presence of the surfactant. As the bubble diameter increases, the rising velocity increases and bubble deformation becomes significant. The variations of the bubble velocity and shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The rising bubble technique was employed to measure the aspect ratio and the terminal rise velocity (V T ) of bubbles as such two factors have been widely acknowledged to evaluate the surface mobility under different conditions. 22 It is obvious that when V T is reached during the bubble rising stage, there exists a force balance between the buoyancy (F B ) and hydrodynamic drag force (F D ) shown in eq 1. When the freerising bubbles are rendered immobile, the V T values should be decreased.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The rising bubble technique was employed to measure the aspect ratio and the terminal rise velocity (V T ) of bubbles as such two factors have been widely acknowledged to evaluate the surface mobility under different conditions. 22 It is obvious that when V T is reached during the bubble rising stage, there exists a force balance between the buoyancy (F B ) and hydrodynamic drag force (F D ) shown in eq 1. When the freerising bubbles are rendered immobile, the V T values should be decreased.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The smart budget solution allowing us to avoid using the additional came integration of a vision system with a set of mirrors [29][30][31], as presented in Figur Figure 2. Schematic top-view of experimental set-ups for tracking bubble movement equip mirrors used by: (A) Lunde and Perkins [29] and (B) Zhang et al [30] and Luo et al [31].…”
Section: Experimental Methods To Study Bubble Motionmentioning
confidence: 99%
“…In 'contaminated' (SAS) liquids, the bubble of with either a zig-zag or a spiral path [25][26][27]; thus, an additional camera, placed 9 zontally to the first camera, might be useful for improved tracking of bubble mo [28]. The smart budget solution allowing us to avoid using the additional came integration of a vision system with a set of mirrors [29][30][31], as presented in Figur Figure 2. Schematic top-view of experimental set-ups for tracking bubble movement equip mirrors used by: (A) Lunde and Perkins [29] and (B) Zhang et al [30] and Luo et al [31].…”
Section: Experimental Methods To Study Bubble Motionmentioning
confidence: 99%
“…Therefore, researchers have investigated the evolution of bubbles after changes in surface tension by adding surfactants. Luo et al 37 found that by adding Cetyltrimethylammonium bromide (CTAB) to the electrolyte, the bubble rising speed decreased and the bubble shape tended to be spherical. Monzon et al 38 added tetraalkylammonium cation (TXA +) during electrolysis and found that the frequency of bubble detachment is related to the inhibition of bubble coalescence and flow.…”
Section: Nomenclaturementioning
confidence: 99%